2022
DOI: 10.1039/d1na00712b
|View full text |Cite
|
Sign up to set email alerts
|

Predictive high-throughput screening of PEGylated lipids in oligonucleotide-loaded lipid nanoparticles for neuronal gene silencing

Abstract: Development of a high throughput screening workflow to characterize the impact of unique PEG-lipid parameters on oligonucleotide-loaded lipid nanoparticle structure and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 87 publications
1
42
0
Order By: Relevance
“…Theoretically, an N/P ratio near or slightly lower than 1 (charge balance point) would ensure relatively high loading capacity while saving cargo inputs by reducing the unloaded concentrations. However, determination of the optimal formulation condition requires more evaluations of other formulation attributes and downstream efficacy outcomes. Here, we demonstrated the LWR model can robustly predict % loading of nucleic acid cargoes in LNPs and rank their loading capacity in the 1st-tier HTS scenario, facilitating a facile and automated in-line quality assessment of LNP formulations.…”
Section: Resultsmentioning
confidence: 95%
“…Theoretically, an N/P ratio near or slightly lower than 1 (charge balance point) would ensure relatively high loading capacity while saving cargo inputs by reducing the unloaded concentrations. However, determination of the optimal formulation condition requires more evaluations of other formulation attributes and downstream efficacy outcomes. Here, we demonstrated the LWR model can robustly predict % loading of nucleic acid cargoes in LNPs and rank their loading capacity in the 1st-tier HTS scenario, facilitating a facile and automated in-line quality assessment of LNP formulations.…”
Section: Resultsmentioning
confidence: 95%
“…This suggests the potential for small-scale automated screening of drug formulations followed by translation and scale-up of production methods. This was further demonstrated in a follow-up study using the same automated high-throughput workflow to identify optimal LNP formulations for gene silencing [42]. Similar high-throughput approaches have also been used to screen and prepare LNPs encapsulating mRNA, as well as to improve methods of quantifying the loading of nucleic acid cargos [43,44].…”
Section: Laboratory Automation -Strengthening Data Productionmentioning
confidence: 95%
“…20 Miniaturization of the nanoprecipitation process onto a 96-well plate format using a liquid handling robot has been reported in an effort to screen the lipid composition for mRNA-loaded lipid nanoparticles. 21,22 Moreover, it has also been demonstrated that nanomedicines screened in this manner can be scaled up on microfluidics platforms, thus eradicating potential downstream manufacturing concerns. 21,22 It is straightforward to envision the development of similar workflows for small molecules, proteins, or peptides given the necessary equipment to characterize the resulting nanomedicines.…”
Section: A Physical Platform For High-throughput Nanoparticle Develop...mentioning
confidence: 99%
“…21,22 Moreover, it has also been demonstrated that nanomedicines screened in this manner can be scaled up on microfluidics platforms, thus eradicating potential downstream manufacturing concerns. 21,22 It is straightforward to envision the development of similar workflows for small molecules, proteins, or peptides given the necessary equipment to characterize the resulting nanomedicines. For instance, drug loading capacity (DLC) and encapsulation efficiency (EE) can be automated with appropriate extraction methods and analysis via high-pressure liquid chromatography (HPLC).…”
Section: A Physical Platform For High-throughput Nanoparticle Develop...mentioning
confidence: 99%
See 1 more Smart Citation